Fiscal Policy and Growth of Real Economic Activities in Nigeria (1980-2016) - Salako, Gbadebo; Oyeleke, Olusola Joel (Asian Journal of Economics and Empirical Research, 2019)
Several empirical studies have investigated the effect of fiscal policy on various macroeconomic variables such as inflation, debts, interest rates, unemployment and growth (GDP) for diverse economies, using variant methods. This paper examined the influence of fiscal policy on growth of real economic activities in Nigeria from 1980-2016, using 2010 as base year to adjust for price level. Secondary data sourced from Central Bank of Nigeria (CBN) (2016) were analysed. After verifying the stationarity property of the variables, Johansen cointegration test result revealed evidence of long run relationship among public revenues, expenditure, real GDP and inflation. The results from Vector Error Correction Method (VECM) showed that government expenditure positively and significantly impacted real economic activities’ growth, but converse was the effect of public revenues on RGDP. The results, therefore, imply that government should cut tax to increase disposable income which has aptitude to enhance real aggregate production in Nigeria.